An indigenous solution to deforestation in the Amazon - Liz Kimbrough (The UNESCO Courier, 2023)
“If the forest is still standing, it is thanks to the presence of indigenous peoples. And today, this is the most important mission of our planet. Because it is a mission that not only guarantees our lives but guarantees the lives of all people,” Txai Suruí, activist of the Paiter Suruí people and coordinator of the Indigenous youth movement of Rondônia, Brazil, said in a recent statement.